MEMAHAMI EFEKTIVITAS E-SAMSAT SEBAGAI MEDIA PEMBAYARAN PAJAK KENDARAAN BERMOTOR - Aini, Nur; Furqon, Ihmada Khoiri (JURNAL PERPAJAKAN, 2023)
Overcoming In order to improve the performance of effective public services, a new program was created, namely E-Samsat. E-Samsat is the government’s breakthrought in providing services for the community to fulfill their obligations in paying the motor vehicle tax they have. E-Samsat payment servics can be via sms banking or transfer via an ATM machine. The four main goals of E-Samsat are simple, fast, qualit and safe. This study aims to determine the effectiveness of E-Samsat receipt as a medium for payment of motor vehicle taxes. The research method used by the author tries to describe and review the understanding of the effectiveness of E-Samsat as a medium for paying motor vehicle taxes. Keyword : Tax, E-Samsat